2018
DOI: 10.3389/fmicb.2018.02344
|View full text |Cite
|
Sign up to set email alerts
|

Response of Gut Microbiota to Dietary Fiber and Metabolic Interaction With SCFAs in Piglets

Abstract: Dietary fiber (DF) is increasingly thought to regulate diversity of piglet gut microbiota to alleviate weaning stress in piglets. This study was conducted to investigate the effects of DF on growth performance of piglets and composition of their gut microbiota, as well as the interaction between gut microbiota and short-chain fatty acids (SCFAs) in piglets. A total of 840 piglets were allocated to three dietary treatments consisting of a control group (CG), an alfalfa meal group (AG), and a commodity concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 49 publications
5
70
1
1
Order By: Relevance
“…In the current study, it was observed that peak areas were significantly higher in the controls than treatment groups in all measured SCFA. The alfalfa treatment demonstrated a significant decrease in SCFA concentrations and peak areas in contrast to findings by Liu et al [32], who indicated that alfalfa meal treatment could produce more SCFA and improve piglet gut health, which was associated with less diarrhea. This may be dependent on the age of the pig and the level of feeding.…”
Section: Discussioncontrasting
confidence: 90%
“…In the current study, it was observed that peak areas were significantly higher in the controls than treatment groups in all measured SCFA. The alfalfa treatment demonstrated a significant decrease in SCFA concentrations and peak areas in contrast to findings by Liu et al [32], who indicated that alfalfa meal treatment could produce more SCFA and improve piglet gut health, which was associated with less diarrhea. This may be dependent on the age of the pig and the level of feeding.…”
Section: Discussioncontrasting
confidence: 90%
“…However, the effects of dietary ber supplementation on growth performance in pigs are inconsistent. 36 Many studies have indicated that high dietary ber supplementation increased growth, [51][52][53] while others observed no impact on growth performance. 29,30,54 The changes in the gut milieus and nutrient digestion can improve the gut microbial composition, production performance, and health of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…35 The diarrhea incidence (%) was calculated using the method. 36 The acetate, butyrate, propionate, and the total SCFAs were analyzed according to the method described. 37…”
Section: Growth Performance Diarrhea Incidence and Scfasmentioning
confidence: 99%
“…34 A species rarely reported in dogs, "Helicobacter winghamensis," was isolated from fecal samples of working farm dogs. 38 Effects of host genetics and environmental conditions on fecal microbiota composition in pigs revealed that sanitary stress was of relatively minor influence on microbiota composition in high or low residual feed intake pigs although there was an increase in the abundance of Helicobacter in low residual feed intake pigs subjected to stress. 36 Weaning is a crucial period leading to serious intestinal dysbiosis and mortality in piglets.…”
Section: Pre S En Ce Of Non -H Elicobac Ter Pylori Helicobac Ter S mentioning
confidence: 99%
“…A 30-day feeding trial of piglets with alfalfa meal or commodity concentrated fiber resulted in an improvement in gut health associated with a lower relative abundance of Helicobacter, potentially explaining the reduction of piglet diarrhea. 38 Effects of host genetics and environmental conditions on fecal microbiota composition in pigs revealed that sanitary stress was of relatively minor influence on microbiota composition in high or low residual feed intake pigs although there was an increase in the abundance of Helicobacter in low residual feed intake pigs subjected to stress. 39 Idiopathic chronic diarrhea (ICD) is a common cause of morbidity and mortality among juvenile rhesus macaques.…”
Section: Pre S En Ce Of Non -H Elicobac Ter Pylori Helicobac Ter S mentioning
confidence: 99%